2014
DOI: 10.1111/ases.12105
|View full text |Cite
|
Sign up to set email alerts
|

Colorectal resection in nonagenarians: Effectiveness of laparoscopic surgery

Abstract: Laparoscopic surgery is considered an extremely useful treatment for very old patients because it has a low risk of postoperative complications, even in the presence of pre-existing diseases. We conclude that LAC may be indicated in nonagenarians.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 23 publications
0
8
0
Order By: Relevance
“…Only five series have been reported in which nonagenarians with CRC have been exclusively included and most of them with a small number of patients [8][9][10][11][12]. Some other studies have differentiated the characteristics of nonagenarians but in the context of large series that mainly include octogenarians [2,13,14].…”
Section: Introductionmentioning
confidence: 99%
“…Only five series have been reported in which nonagenarians with CRC have been exclusively included and most of them with a small number of patients [8][9][10][11][12]. Some other studies have differentiated the characteristics of nonagenarians but in the context of large series that mainly include octogenarians [2,13,14].…”
Section: Introductionmentioning
confidence: 99%
“…Given the potential for cure with surgery, however, patients and their families often choose surgery over conservative, but less curative, treatment, particularly in the emergency setting. While surgical resection for colorectal cancer offers the best chance of survival in most age groups, 30‐day mortality and long‐term survival data in patients ≥ 90 years of age is limited to a handful of small studies .…”
Section: Introductionmentioning
confidence: 99%
“…There have been many reports regarding laparoscopic surgery for colorectal cancer in very elderly patients . They have demonstrated that laparoscopic colectomy is a feasible and safe option.…”
Section: Discussionmentioning
confidence: 99%